More than Sports Participation: The Role of Ground Reaction Force, Osteocalcin and Lean Soft Tissue on Bone Density Accrual in Adolescents: ABCD Growth Study - Maillane-Vanegas, Santiago [UNESP]; Luiz-de-Marco, Rafael [UNESP]; Narciso, Pedro Henrique [UNESP]; Faustino-da-Silva, Yuri Ventura da Silva [UNESP]; Kemper, Han; Ribeiro Agostinete, Ricardo [UNESP]; A Fernandes, Rômulo [UNESP] (Elsevier, 2022)
The objective of this study was to identify predictors of 12-mo areal bone density accrual in different body segments, lean soft tissue, and osteogenic characteristics attributed to sports participation among adolescent girls and boys. Adolescents (Girls [n = 64], [aged = 14.7]); Boys [n = 129], [aged = 14.6]) were stratified into three groups according to their engagement in different sports (Control [n = 68], Swimming [n = 25], and Weight-bearing sports [n = 100]). Areal bone density (aBMD [g/cm²]) and lean soft tissue (LST) [kg] were measured by dual-energy x-ray absorptiometry (DXA; Lunar DPX-NT; General Electric Healthcare, Little Chalfont, Buckinghamshire, United Kingdom). The ground reaction force (GRF) index attributed to sports participation (Sport-GRF) was created considering the GRF attributed to each sport, body weight of the adolescent, and the amount of time spent in sports participation. Osteocalcin levels (ng/mL) were estimated from a venous blood sample. Multiple regression analysis showed that after adjusting for covariates, the models involving sport-GRF, LST (Δ), and osteocalcin explained 15.8% to 76.2% of the aBMD gains. Specifically in girls, OC was only associated with lower limb aBMD accrual. In boys, however, sport ground reaction forces were positively associated with total spine aBMD accrual. Furthermore, the LST (Δ) was positively associated with aBMD accrual in all body sites (β = 0.003 to 0.011) in both sexes. Increases in LST contributed significantly to gains in aBMD accrual in both sexes, being a more important predictor of changes in bone outcomes than ground reaction forces and osteocalcin.
Keywords: Bone mineral density; lean soft tissue; osteocalcin; sport ground reaction force; sports